1992
DOI: 10.1209/0295-5075/19/5/011
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of the Electrical Conductivity of Ultrathin Amorphous Palladium Films

Abstract: The temperature-dependent electrical conductances of sets of ultrathin amorphous Pd fdms prepared by successive deposition in situ a t low temperatures have been found to scale over a range of conductances encompassing both the strongly and weakly localized regimes. This scaling, as well as the variation of the scaling parameter with the Boltzmann conductance, suggests a unified picture of the insulator-to-metal transition in two dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…The temperature dependence of the resistance has been studied in ultrathin quench-condensed films of Ag, Bi, Pd [8] and Pb [24,25]. The films were deposited on liquid helium cooled substrates and resistance measurements were performed in situ at temperatures down to 0.15K.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature dependence of the resistance has been studied in ultrathin quench-condensed films of Ag, Bi, Pd [8] and Pb [24,25]. The films were deposited on liquid helium cooled substrates and resistance measurements were performed in situ at temperatures down to 0.15K.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Efros and Shklovskii (ES) showed that including Coulomb interactions between electrons results in a soft gap in the density of states at the Fermi energy, which changes the variable range hopping exponent to x = 1/2 in all dimensions [2]. Hopping conduction has been investigated in a wide variety of materials, such as doped semiconductors [3,4], semiconducting heterostructures [5], amorphous metals [6][7][8][9][10], magnetic materials [11] and superconductors [12]. Both the Mott and the ES forms of variable range hopping have been observed, as well as a crossover between the two regimes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies of two-and three-dimensional systems, 17,20,41,42,60,77,78 but by far not in all such investigations, the identification of insulating samples has been facilitated by empirical scaling of s(T, x D const.) curves,…”
Section: Breakdown Of Scaling Of T Dependences Of σmentioning
confidence: 99%
“…(5) very likely indicates the transition; for a detailed reasoning see Appendix B. This criterion has a great advantage over the approaches discussed in the previous subsections: In a scaling analysis, the reduced temperature, T/T 0 , may vary over several orders of magnitude, compare Figure 4 in M€ obius et al 20 and Figure 2 in Liu et al 77 Thus, the reliability of s(T ! 0) extrapolations and the trustworthiness of sample classifications close to the MIT can be considerably improved by utilizing the scaling relation Eq.…”
Section: Breakdown Of Scaling Of T Dependences Of σmentioning
confidence: 99%
See 1 more Smart Citation